2023
DOI: 10.3390/jfb14070334
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Future Perspectives for Additively Manufactured Polylactic Acid Using Fused Filament Fabrication in Dentistry

Abstract: Additive manufacturing (AM), which is also called rapid prototyping/3D printing/layered manufacturing, can be considered as a rapid conversion between digital and physical models. One of the most used materials in AM is polylactic acid (PLA), which has advantageous material properties such as biocompatibility, biodegradability, and nontoxicity. For many medical applications, it is considered as a leading biomaterial. In dentistry, in addition to its uses in dental models (education, teaching, simulation needs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…The use of the developed RBTO approaches allows to provide the best compromise between their weight and rigidity. When developing the RBTO approaches for this area, the applications to cellular structures can be extended to cover surgical operations in dentistry (maxilla and mandible) [36]. A cellular structure can be optimized to be used between the fracture's surfaces to replace the lost bone part considering the advanced strategies in RBTO model.…”
Section: Future Work and Perspectives For Rbto Approachesmentioning
confidence: 99%
“…The use of the developed RBTO approaches allows to provide the best compromise between their weight and rigidity. When developing the RBTO approaches for this area, the applications to cellular structures can be extended to cover surgical operations in dentistry (maxilla and mandible) [36]. A cellular structure can be optimized to be used between the fracture's surfaces to replace the lost bone part considering the advanced strategies in RBTO model.…”
Section: Future Work and Perspectives For Rbto Approachesmentioning
confidence: 99%
“…In SLA, a UV-sensitive liquid resin that selectively hardens when a material surface is exposed to a UV laser beam is employed [4], while in SLS, a laser is used as the energy source to selectively sinter a powdered material, solidifying it. FDM is a useful technique thanks to its geometric flexibility and low cost; with this technique, it is possible to produce polymer prostheses with hollow, semi-hollow, and solid structures, allowing the easy fabrication of various dental applications [5]. The SLS technique, on the other hand, can also be used to cast various metal alloys, including for metal frameworks for dentures, crowns, and dental implants, while the polymers used in SLS are usually applied in the manufacture of surgical guides and dental models [6].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers have many developing different applications in the medical field [1][2][3][4]. In recent years, research on environmentally friendly polymeric designs for biomaterials has become increasingly widespread around the world [5][6][7][8]. For instance, it has been reported that an L-lysine-loaded poly(lactic-co-glycolic acid) (PLGA) microparticle system, which supports cell proliferation and angiogenesis, has been developed as a nontoxic, biocompatible, and cost-effective microparticle system for rapid vascularization [9].…”
Section: Introductionmentioning
confidence: 99%